Perbedaan Jumlah Hitung Osteoblas pada Pergerakan Ortodontik Gigi Setelah Pemberian Jintan Hitam - Darman, Setyah Sultrasari; Handayani, Fani Tuti; Hartomo, Bambang Tri; Logamarta, Setiadi Warata; Sari, Dwi Nur Indah (Fakultas Kedokteran Gigi Universitas Jember, 2024)
Osteoblasts are important for orthodontic tooth movement because they influence the activity of bone formation on the tension area. The administration of natural ingredients such as black cumin is proven to increase the number of osteoblasts because it contains thymoquinone as antioxidants to accelerate the process of tooth movement. The study aims to determine the differences in osteoblast count and their effect on the orthodontic movement of teeth after oral administration of black cumin. The method used in this research is experimental laboratory in vivo with a randomized post-test only control group design using 16 male Sprague-Dawley rat samples that were devided into four groups: the control group (K) with distilled water for 7 and 14 days, also the treatment group (P) with black cumin (Nigella sativa) for 7 and 14 days Elastomeric separators were placed on the upper jaw central incisors (right central incisor) using a separator applier to provide orthodontic mechanical force conditions. Alveolar bone tissue samples were taken after treatment then the number of osteoblasts was calculated histologically. Data were anaylzed using One Way Anova Test and LSD (p<0.05). Result of this research indicated that there was an increase in the number of osteoblasts in orthodontic movement after oral administration of black cumin.